Implementation Network Nerves Imitation Using the Backpropagation Method For Prediction Sale Groceries - Nuraitul Janah , Siti; Hastono , Tri; Nurmala, Nurmala; Nor Azhari Azman, Mohamed (APPLIED SCIENCE AND TECHNOLOGY REASERCH JOURNAL, 2023)
Abstract The sale of groceries is one of the important things _ in the retail industry, Predicting the sale of groceries accurately can help the company in planning supplies, and making decisions for business. In implementing network nerves imitation backpropagation method as tool predictions For sale basic food.Method This can used To practice network nerve imitation to recognize patterns and relationships between influencing factors _ _ in the sale of groceries, like price, promotion, and economic factors. Data sale collected groceries _ from periods previously used as a training dataset For practice network nerves imitation. Aside from That For shows that implementation network nerves imitation with backpropagation method can give predictions of sales enough basic necessities accurate predictions This is also used by other companies for optimizing inventory, managing promotional strategies, and responding to change conditions company with more effectively. .